Rheumatic heart disease in Uganda: predictors of morbidity and mortality one year after presentation. Issue 1 (December 2017) - Okello, Emmy; Longenecker, Chris; Beaton, Andrea; Kamya, Moses; Lwabi, Peter
Abstract Background Rheumatic heart disease (RHD), the long-term consequence of rheumatic fever, accounts for most cardiovascular morbidity and mortality among young adults in developing countries. However, data on contemporary outcomes from resource constrained areas are limited. Methods A prospective cohort study of participants aged 5–60 years with established RHD was conducted in Kampala, Uganda, in which clinical exam, echocardiography, electrocardiography (ECG), and laboratory evaluation were done every 3 months and every 4-week benzathine penicillin prophylaxis was prescribed. Participants were followed up for 12 months and outcomes and predictors of morbidity and mortality were assessed using Kaplan Meier curves and Cox proportional hazards models. Results Of 449 subjects, 66.8% (300/449) were females, median age was 30 (interquartile range 20). 73.7% (331/449) had atleast one follow up visit. Among these, 35% (116/331) developed decompensated heart failure and, 63.7% (211/331) developed atrial fibrillation. Heart failure was associated with poor penicillin adherence (OR = 3.3, CI 2–5.4, p  = 0.001), and left ventricular end diastolic diameter greater than 55 mm (OR = 3.16, CI 1.73–5.76, p  = 0.001). Atrial fibrillation was associated with left atrial diameter >40 mm (OR = 7.5, CI 2.4–9.8, p  = 0.001). There were 59 deaths with a 1-year mortality rate of 17.8%. Most deaths occurred within the first three months of presentation. Subjects whose average adherence to benzathine penicillin was <80% had significantly greater mortality (31% vs. 9%, log rankp  < 0.001). In multivariate analysis, the risk of death among those with poor penicillin adherence was 3.81 times higher than those with better adherence (HR = 3.81, CI 1.92–7.63, p  = 0.001). Other predictors of 1 year mortality included heart failure (HR 8.36, CI 3.28–21.31, p  = 0.001) and left ventricular end diastolic diameter greater than 55 mm (HR = 1.93, CI 1.07–3.49, p  = 0.02). Conclusion In this study of RHD in Uganda, morbidity and mortality within 1 year of presentation were higher than in recently published from other low and middle income countries. Suboptimal adherence to benzathine penicillin injections was associated with incident heart failure and mortality over 1 year. Future studies should test interventions to improve adherence among patients with advanced disease who are at the highest risk of mortality.